Kazakhstan and the SCO: main results and problems of cooperation - Айтенов, Н. Ж. (Journal of Oriental Studies, 2018)
The article considers cooperation of the Republic of Kazakhstan and the Shanghai cooperation organization (SCO) and the prospects for its further development. The SCO is a promising integration structure, so the Republic of Kazakhstan takes an active part in its activities, being one of the founders of the organization. In the realities of the globalized world the creation of the Shanghai cooperation organization is the answer to challenges and threats. And the further development of cooperation between the member states of the organization aimed at the formation of a fair world order based on mutually beneficial relations represents a significant interest in the activities of the SCO. The SCO is characterized as an instrument of political, military and economic cooperation among member states, identified the main results of activities and problems of further cooperation of member states within the framework of this organization.